Toksisitas dan Anti-inflamasi Senyawa 1,5-Bis(3’-Etoksi-4’-Hidroksifenil)-1,4- Pentadien-3-on (EHP) - ESTI MUMPUNI; LESTARI RAHAYU; ARIEF NURROCHMAD (Fakultas Farmasi Universitas Pancasila, 2015)
The 1,5-bis(3’-ethoxy-4’-hydroxyphenyl)-1,4-pentadiene -3-one (EHP) is a curcumin analogue. The structure has also been identified before. EHP is obtained, which has been pharmacologically proven to have higher antioxidant activity than curcumin. The objectives of this research were to determine the acute toxicity (LD50) of EHP compound by Weil C.S. method using male mice as experimental animals and to determine its antiinflammatory activity. The LD50 value of the synthesized EHP compound is 6,8675 g/kg body weight (bw) with the criteria of mild toxic, so it is assumed to be safe as drug substance candidate. The anti-inflammatory activity of the compound was determined by obeserved legs swelling index of the mouse. Anti-inflammatory activity of EHP with doses of 137.35 mg, 274.70 mg and 549.40 mg were equal to aspirin with the dose of 90 mg/200 g bw